Entre o fracasso e o sucesso escolar: os forasteiros de Cumuruxatiba-BA - Santos, Glauco Fernando Silva (2022)
This thesis investigates the pedagogical attitudes of educators who decided throughout their lives to experience new ways of working far from their homeland and their professional training environment. Thus, foreign educators, as they are known, experience school failure and seek solutions, sometimes “clandestine” for the success of subjects throughout schooling. In this way, we intend to understand, through semi-open interviews, how teachers build possibilities to resist the strategies of the school apparatus in disseminating the dominant ideology, and what are the possible solutions taking into account the problem of the educational weight of cultural capital and the socially selection of the school system. The work proposes theoretical reflections based on critical theories, mainly under the light of scholars of the sociology of education and critics of the capitalist education system, to understand the agents of cultural exclusion present in school practices. Therefore, we propose a dialogue with "outsiders" educators who work in the education of Cumuruxatiba, district of Prado, municipality in the extreme south of the state of Bahia, in order to raise hypotheses about school failure and success in a pluricultural context.(AU)